Mujer y corte entre la Edad Media y el Renacimiento: nuevas líneas de investigación - Nuria Aranda García; Almudena Izquierdo Andreu (Atalaya)
The aim of this paper is to present the monograph on the literary role of women at court between the Middle Ages and the Renaissance. First of all, the monograph is presented including the goals and lines of research, then followed by the thematic blocks and a list of the authors. A broad overview is given of women in books of chivalry, convent literature and women as texts' dedicatees. Secondly, a review of each work is given, highlighting the main novelties, ending up with a conclusion and future lines of work.